2010
DOI: 10.1111/j.1475-6765.2009.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐based voting in the parliamentary elections of 2007 in Finland

Abstract: In contrast to many other countries, the Finnish open‐list proportional representation (PR) system with its mandatory preferential voting provides an opportunity to study gender‐based voting empirically. Using the 2007 Finnish national election study, the article presents an analysis of the grounds for same‐gender voting, including motivations related to descriptive and substantive dimensions of representation. None of the motivations is able to account men's higher propensity to vote for a candidate of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 25 publications
(50 reference statements)
3
56
1
1
Order By: Relevance
“…Those who say the genders are equal on the economy are somewhat but not significantly more likely to say they voted for a woman than those with pro-male stereotypes. In addition, women are more likely than men to support women candidates, confirming findings from Europe and the Americas (Fulton 2014;Goodyear-Grant and Croskill 2011;Holli and Wass 2010;Morgan 2015;Paolino 1995;Seltzer, Newman, and Leighton 1997;Simon and Hoyt 2008). Do results vary from one country to another?…”
Section: Resultssupporting
confidence: 82%
“…Those who say the genders are equal on the economy are somewhat but not significantly more likely to say they voted for a woman than those with pro-male stereotypes. In addition, women are more likely than men to support women candidates, confirming findings from Europe and the Americas (Fulton 2014;Goodyear-Grant and Croskill 2011;Holli and Wass 2010;Morgan 2015;Paolino 1995;Seltzer, Newman, and Leighton 1997;Simon and Hoyt 2008). Do results vary from one country to another?…”
Section: Resultssupporting
confidence: 82%
“…This is in fact a very interesting finding given that in the Finnish parliamentary elections of 2003, 63 per cent of voters voted for a candidate of the same gender and 42 per cent for a candidate of approximately the same age (Bengtsson & Grönlund 2005, 241). In 2007, the corresponding figure for same-gender voting was also 63 per cent (Holli & Wass 2009). …”
mentioning
confidence: 98%
“…Previous studies have indicated gender differences in the political behaviour of the electorate. Gender differences in party choice and voting are found both in presidential-style systems such as the United States and in parliamentarian systems allowing the electorate to vote for a specific candidate (Zipp & Plutzer 1985;Huddy & Terkildsen 1993a;Plutzer & Zipp 1996;Sanbonmatsu 2002;Holli & Wass 2010;Giger et al 2014). Gender gaps in voting patterns might result from differences in ideological positions and policy opinions (see, e.g., Togeby 1994;Studlar et al 1998;Inglehart & Norris 2000), perception of sex roles (Hershey 1977(Hershey , 1980, as well as gender identity and gender stereotyping focused upon here.…”
Section: Gender and Party Leadershipmentioning
confidence: 99%